2022
DOI: 10.5213/inj.2142408.204
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of the Recurrence Characteristics of Hunner Lesion After Repeated Transurethral Ablation in Patients With Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Purpose: The aim of this study was to investigate the rate and pattern of recurrence for patients with Hunner lesion (HL) type interstitial cystitis/bladder pain syndrome (IC/BPS) after transurethral ablation.Methods: This prospective study included 210 patients with HL type IC/BPS. The primary outcomes were the recurrence rate according to 3 patterns of recurrence: pattern A (according to the relationship with the previous surgical site), pattern B (according to the bladder zone), and pattern C (according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Het effect van ablatie is meestal tijdelijk. De Hunnerse laesies komen terug, soms op dezelfde plek, soms in randen van het litteken en soms ook op ander plekken, en hiermee meestal ook de klachten [32]. IC zelf geeft fibrose en contractuurvorming, maar de herhaaldelijke ablaties ook.…”
Section: Behandeling Keene Beschreef In 1920 Een Open Excisie Van Eenunclassified
“…Het effect van ablatie is meestal tijdelijk. De Hunnerse laesies komen terug, soms op dezelfde plek, soms in randen van het litteken en soms ook op ander plekken, en hiermee meestal ook de klachten [32]. IC zelf geeft fibrose en contractuurvorming, maar de herhaaldelijke ablaties ook.…”
Section: Behandeling Keene Beschreef In 1920 Een Open Excisie Van Eenunclassified
“…We conducted a similar prospective study involving 210 patients with Hunner lesions to investigate the recurrence patterns of these lesions. 21 Interestingly, our study revealed that recurrence could occur at any location within the bladder wall after repeat ablation, regardless of the site or number of lesions.…”
Section: Limitation Of Transurethral Ablationmentioning
confidence: 55%
“…In addition, the study assessed Hunner lesion recurrence following transurethral ablation and revealed that 21.8% of lesions recurred at the previous ablation site, 18.8% at a new site, and 59.4% at both the previous and new sites. We conducted a similar prospective study involving 210 patients with Hunner lesions to investigate the recurrence patterns of these lesions 21 . Interestingly, our study revealed that recurrence could occur at any location within the bladder wall after repeat ablation, regardless of the site or number of lesions.…”
Section: Transurethral Ablation (Resection or Coagulation)mentioning
confidence: 89%
“…Notably, these histological changes can be observed in the entire bladder and are not confined to the Hunner lesions 7 . Even when the recurrence pattern was prospectively observed after endoscopic ablation, most recurrences of Hunner lesions occurred in the vicinity of the ablation site, but the rate of recurrence at new sites reaches about 50% 17 . For severe pain caused by Hunner lesions, symptom relief may be maintained for a while by ablation of the Hunner lesions.…”
Section: Discussionmentioning
confidence: 99%